Nuclear aberrations in the gingival epithelium of patients with chronic periodontitis - Olga Vasil'evna Serikova; Bogdan Romanovich Shumilovich; Zoya Alexandrovna Filippova; Vladislav Nikolaevich Kalaev; Elena Anatol'evna Kalaeva; Anna Viktorovna Larina (Wolters Kluwer Medknow Publications, 2023)
Context: Periodontitis characterized by mild symptoms in the early stages, which makes diagnostics problematic. The gingival epithelium can be used for micronucleus assay since gums are the area affected by the disease. Aims: The aim of the study was to study the frequency of occurrence and the range of nuclear anomalies in gingival epithelium of healthy people and people with periodontitis. Settings and Design: Scrapings of the gingival epithelium were made next to the central incisors (1.1) and molar teeth (1.7) in control and experimental groups (ten healthy males 35-50 years old and 10 males with periodontitis). Materials and Methods: The preparations were stained by Romanowsky-Giemsa. The frequency of nuclear aberrations (‰), the accumulation index, and the repair index were determined. Statistical Analysis Used: The differences in the medians of nuclear aberrations were determined using Wilcoxon and the Van-der-Waerden tests. The pathology proportions were compared using the Z-test. To determine the predictors of periodontitis, receiver operator characteristic analysis was used. For multiple comparisons, the Bonferroni correction was used. Results: In the experimental group, the range of nuclear aberrations was wider, the ratio of karyolysis in the unaffected area was higher, than that in control; perinuclear vacuoles were fewer and macronuclei were more in the affected area. The frequency of cells with micronuclei over 1.33‰ in the affected area is the periodontitis marker. Conclusions: Gingival epithelium can be used in micronucleus assay. Micronucleus test revealed a wider range of nuclear aberrations in the cells of the gingival epithelium and a higher frequency of occurrence of micronuclei in patients with periodontal disease compared to healthy subjects. Therefore, cytological signs of the inflammation appear earlier than the clinical ones and are verified more clearly. The markers of apoptosis and destruction of nuclei, and low repair index indicate normal elimination of damaged cells. An increased accumulation index in people with periodontitis may indicate the risk of malignant tumors.